Perbedaan Perlilaku Social Loafing Ditinjau Dari Big Five Personality Theory Pada Mahasiswa Fakultas Psikologi Universitas Medan Area - Isnaini Hasanah; Babby Hasmayni (Universitas Medan Area, 2022)
This study aims to determine the differences in Social Loafing behavior in terms of the Big Five Personality of psychology faculty students at Medan Area University. The problem was focused on Social Loafing behavior that occurs in 2018 2019 students. To approach this problem, the theoritical references from Myers Twenge and Cervone Pervin is used. The data was collected through google form and analyzed quantitatively. Subjects were 64 people, with a sampling technique, namely Accidental Sampling. The measuring instrument used in this research was the Social Loafing scale and the TIPI (Ten Item Personality Inventory) scale. Data analysis was performed using SPSS with the One Way Anova technique. This study concludes that there were significant differences in Social Loafing behavior (F = 9,284; Sig = 0.000 0.050) in terms of the Big Five Personalities, with Neuroticism has the highest mean (37.67) while Conscientiousness has the lowest mean (23,92).